Peran Kepemimpinan Kepala Madrasah dalam Mendisiplinkan Guru di MTs Negeri 1 Kepahiang - Bastian, Dian; Asha, Lukman; Baryanto, Baryanto (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2024)
The focus of this research is on common rule violations committed by some educators in schools such as being late, leaving early, and attending to personal matters during work hours. The study aims to describe how the head of the Islamic Junior High School plays a crucial role in managing the discipline of teachers at State Islamic Junior High School 01 Kepahiang. The research method used is qualitative with data collection techniques including observation, interviews, documentation, and data validation through triangulation method. Data analysis is based on Miles and Huberman's opinion, involving data reduction, data presentation, and drawing conclusions. The research findings reveal that the head of State Islamic Junior High School 01 Kepahiang has seven important roles in enhancing the work discipline of educators. The head of the school acts as an educator by demonstrating personal discipline to set an example for subordinates. As a manager, the head of the school conducts regular evaluations and coordination to maintain discipline. As a leader, the head of the school guides and motivates all parties towards the school's goals. As a supervisor, the head of the school supervises and controls to improve discipline with a familial approach. As an innovator, the head of the school provides facilities that support teachers in their tasks. As an administrator, the head of the school regularly checks teachers' administration. Lastly, as a motivator, the head of the school rewards and penalizes teachers based on their level of discipline.